The adventures of Sherlock Holmes - Doyle, Arthur Conan, Sir, 1859-1930. (New York, Baronet, 1992)
Contained in this vol.-the Red Headed League; the Copper Beeches,and the Speckled Band.
1080
Keywords: Mystery fiction -- Fiction; Mysteries and miracle plays -- Fiction